(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In this research, Savitribai Phule Pune University’s Balasaheb Thorat College players competing in intercollegiate sports contests may benefit from yoga. Studies on yoga’s effects on sports performance and physical and mental health are examined. It then evaluates how focused yoga practices might be adjusted to the unique demands of varied sports provided at the institution, ranging from strength and endurance sports like cycling to precision sports like archery. Challenges in adoption and measures to encourage excitement among athletes are addressed. The report presents practical ideas for incorporating yoga via pre-game routines, rehabilitation sessions, and devoted practices, stressing the need for individualization. It suggests undertaking pilot studies to test yoga’s efficacy within the college’s specific sporting setting. By emphasising yoga’s many advantages, the study wants to promote acceptance of this ancient practice as a beneficial, holistic training tool for growing well-rounded student athletes.